Implementation of Differentiated Learning to Improve Student Learning Results on Algebra Operations Material - Elya; Supratman; Liska Lestari (Universitas Sulawesi Barat, 2025)
Differentiated learning is an important strategy in the world of education to address the challenges of student heterogeneity, especially in algebraic operations material which requires a strong understanding of concepts and procedures. This research aims to analyze the implementation of differentiation learning in improving student learning outcomes in Mathematics subjects on the subject of Algebra operations. This research uses differentiated learning involving three elements, namely visual, auditory and kinesthetic. This research is classroom action research which is divided into two cycles and begins with a pre-cycle. Each cycle consists of planning, implementing actions, observing, evaluating, and reflecting. The research was carried out on class VIIA odd semester students at MTs Persis Benda for the 2024/2025 academic year. As for the results of research carried out on 31 students, in the pre-cycle activities the number of students who completed was 5 students (16.13%), while 26 students who did not complete it were 26 students (83.87%), with an average score of 51.16. In the first cycle, students experienced an increase, the number of students who completed was 17 students (54.84%) while 14 students who had not completed it were 14 students (45.16%) with an average score of 66.65. Then in cycle II there was a very high increase compared to the previous cycle, namely 28 students who had reached the KKM (90.32%), while 3 students who had not yet completed it, with an average score of 80.71. The results of this research show that the application of differentiated learning can improve Mathematics learning outcomes in algebraic operations material for class VIIA odd semester students at MTs Persis Benda for the 2024/2025 academic year.